Political Autocratization and the Decline of Freedom of Religion or Belief in Indonesia and India: A Comparative Analysis 2016–2025 - Robby, Hadza Min Fadhli; Mulia, Jalaluddin Rizqi; Shafia, Inas Ainun (Universitas Islam Negeri Raden Intan Lampung, 2026)
This research investigates the impact of political autocratization on the protection of freedom of religion or belief within hybrid regimes, specifically focusing on the cases of Indonesia and India. The nature of hybrid regimes—situated between democratic and autocratic systems—makes it difficult to ensure the implementation of human rights norms, particularly those regarding religious freedom. Typically, these protections deteriorate significantly as a result of political autocratization. In the case of Indonesia, a persistent culture of intolerance and a decline in the protection of religious freedom are the consequences of a weakening commitment to a democratic way of life. The existence of elite patronage toward intolerant civil society organizations in several regions, combined with the use of “moderation” discourse as a tool for political control, has left religious freedom increasingly at risk. Furthermore, an autocratic, state- -centered interpretation of Pancasila creates an environment where the state ideology cannot effectively be utilized to guarantee Indonesia’s religious diversity. In India, democracy has faced significant setbacks due to the growing influence of Hindutva ideology across the executive, legislative, and judicial branches of government. While India officially upholds secularism as a state principle, the reinterpretation of this concept under the current regime has sidelined secular norms in favor of a more dominant role for religion in Indian politics.